Corpus stylistics, norms and comparisons: Studying speech in great expectations - Mahlberg, Michaela; Wiegand, Viola (Taylor and Francis, 2018)
This chapter situates corpus stylistics within wider trends in the digital humanities and emphasises the need for developing tools and visualisation methods tailored to the analysis of literary texts. Using the CLiC web app, the chapter shows how standard corpus linguistic methods can be further developed to better address research questions in literary stylistics. The analysis presents an innovative comparative approach to the identification of speech clusters in an individual fictional text-Dickens’s Great Expectations-as compared to larger corpora containing all of Dickens’s novels and authentic spoken language, respectively. This comparative perspective does not only emphasise differences between fictional speech and narration, but also considers overlapping patterns. The chapter links the notions of deviation and norms that are drawn on in literary stylistics to corpus linguistic comparisons of different corpora with particular emphasis on the fuzzy nature of linguistic categories.
CRIS-Team Scopus Importer:2024-03-27